A Comparison of Concrete Slump Test with Different Percentage of Polystyrene and Sawdust Replacement - Mohd.Johari, Muhammad Nur Alif; Yahya, Muhammad Maher Bajrai; Misnan@Adnan, Nur Adebahanim; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2022)
The comparison of replacing natural coarse aggregate with polystyrene and fine aggregate with sawdust on the slump value of concrete is discussed in this study. Ordinary concrete was utilized as a control sample in this study to compare with different percentage replacement of aggregates. The objective of this study was to determine the slump value with different replacements of lightweight material. Furthermore, this study was carried out to obtain the density and mass of concrete with different material replacement rates. Sample preparation involved four types of concrete that were mixed: a control sample, a 5%, 10%, and 15% of polystyrene and sawdust replacement. The slump test, density, and mass measurement were determined to assess the efficacy of replacement material of coarse and fine aggregates in this study. Based on the findings, the slump value is higher for 15% replacement which is 145 mm while for 10% and 5% replacement, the slump value is 75 mm and 0 mm, respectively. This show that the workability of concrete increase with 15% of polystyrene and sawdust replacement.